Modelling of heat transfer In biological tissue by interval FEM - Jasiński, Marek; Pownuk, Andrzej (Computer Assisted Methods in Engineering and Science, 2023)
In this paper, an algorithm of calculation of extreme values of temperature based on interval arithmetic is presented. Many mechanical systems with uncertain parameters can be described by a parameter dependent system of linear equations K()T = B(). Using natural interval extension of a real function, one can transform the system of linear equations into the system of linear interval equations K()T = B(). Solution of the system of linear interval equations always contains the exact solution of the parameter dependent system of equations. A new method of computation of extreme values of mechanical quantities based on the monotonicity test is introduced. This method can give exact solution of a parameter dependent system of equations.